Photoluminescence study of Eu-doped Ga2O3 and GaN nanowires and nanoparticles produced by hydrothermal growth [Articol] - Rusu, Emil; Ursachi, Veaceslav; Culeac, Ion; Raevschi, Simion; Vlazan, Paulina (Editura "Tehnica-UTM", 2015)
We present results on preparation of Eu doped GaN nanoparticles and nanowires on the basis of Ga2O3 nanomaterial produced by hydrothermal growth. The monoclinic Ga2O3 nanoparticles and nanowires have been prepared with gallium nitrate and sodium hydroxide as precursors. nanomaterial produced by hydrothermal growth. The monoclinic Ga2O3 nanoparticles and nanowires have been prepared with gallium nitrate and sodium hydroxide as precursors. The geometrical form on the nanomaterial is determined by the duration of the hydrothermal process. The Ga2O3 nanomaterial is transformed unto GaN nanoparticles and nanowires by nitridation in a flow of NH3 and H2. The photoluminescence properties Eu doped Ga2O3 and GaN nanomaterial are investigated under pulsed and continuum wave excitation. The produced material is also investigated by means of XRD analysis, Raman scattering and Fourier transform infrared (FTIR) spectroscopy.
Keywords: nanoparticles; nanowires; hydrothermal growth; nitridation; luminescence